Evaluasi Kegiatan Budidaya Tanaman Cabai Dipekarangan Menggunakan Pupuk Cair Ekstrak Bawang Merah Di Desa Iwul Kabupaten Bogor - N Nurhasanah; A. Hadian Pratama Hamzah (LPPM STIKOM Tunas Bangsa, 2022)
Iwul Village is located in Parung District, Bogor Regency. This village, especially in RT 01/RW 06, deserves to be used as a place for Community Service activities in the form of using a garden by planting cayenne pepper using liquid organic fertilizer from onion extract. This is because residents in this area have a variety of livelihoods, namely as traders, horticultural farmers, catfish cultivators, and managing fields. Community service in Iwul Village is an effort to improve community skills in processing liquid fertilizer and making optimal use of the yard through chili cultivation. This community service activity is carried out by providing general material, discussions with the community, training, implementation of cultivation, and program sustainability with mentoring schemes by agricultural and environmental experts. After carrying out the program in 2020, measurement results were obtained that describe the community's perception of the program, based on indicators for using yard land to grow crops according to the cayenne pepper that is cultivated is considered appropriate, the people of Iwul Village who are producers of cayenne pepper seeds feel that they are in accordance with the program because the harvest can be sold. In the stalls, the Iwul Village Community as a producer of raw cayenne pepper is considered appropriate by the community, the Iwul Village community as a producer of processed cayenne pepper from garden products is considered appropriate by the community, and the Iwul Village community as a collector and marketer of cayenne pepper production is considered appropriate because they are able to sell garden produce to the surrounding villages. In terms of plant growth, after using extra liquid shallot fertilizer, there was an increase in the fruit yields by 40%. This condition became the basis for increasing the family economy on a micro basis outside of fish farming because there were two business activities carried out by the family.